2008
DOI: 10.1007/s11926-008-0033-6
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic systemic fibrosis: An epidemic of gadolinium toxicity

Abstract: Nephrogenic systemic fibrosis is a devastating systemic fibrosing disorder that afflicts patients with renal dysfunction. Growing evidence supports the hypothesis that gadolinium-containing contrast agents (GCCAs) trigger the development of nephrogenic systemic fibrosis. Hence, this condition is most appropriately called gadolinium---associated systemic fibrosis (GASF). In this report, we review the history of GASF, its association with prior GCCA exposure, its clinicopathologic features, the relevant pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 80 publications
1
25
0
Order By: Relevance
“…The skin changes are often accompanied by other symptoms such as pain, swelling, nausea, vomiting, muscle weakness, and joint stiffness. It also affects other organs and visceral fibrosis of the heart, lungs, and other organs can occur [285]. The first case of NSF was reported in 2000 [286].…”
Section: Nephrogenic Systemic Fibrosis (Nsf)mentioning
confidence: 99%
See 2 more Smart Citations
“…The skin changes are often accompanied by other symptoms such as pain, swelling, nausea, vomiting, muscle weakness, and joint stiffness. It also affects other organs and visceral fibrosis of the heart, lungs, and other organs can occur [285]. The first case of NSF was reported in 2000 [286].…”
Section: Nephrogenic Systemic Fibrosis (Nsf)mentioning
confidence: 99%
“…While the diagnosis of scleromyxedema is confirmed by a positive 7S-IgG paraprotein test, this was characteristically negative in the new disease [286]. It remains challenging to distinguish NSF from other fibrosing disorders and clinical, histopathological, and laboratory test results must be considered to reach a specific diagnosis [285,290]. In 2006, an association of NSF with Gd 3+ -based MRI contrast agents was suggested and subsequently several retrospective analyses of NSF cases revealed that essentially all NSF patients received a Gd 3+ -based contrast agent prior to disease onset [291][292][293][294][295].…”
Section: Nephrogenic Systemic Fibrosis (Nsf)mentioning
confidence: 99%
See 1 more Smart Citation
“…These rheumatic disorders have been well described and carefully studied for many years ( Table 1 ). Gadoliniumassociated systemic fi brosis (nephrogenic systemic fi brosis) is a relatively new but ominous disease affecting patients with chronic kidney disease (CKD) and has been described recently in this journal [ 3 ]. Because the incidence of β 2 -microglobulin amyloidosis has decreased markedly over the past decade, we will not discuss this disorder that previously affected many patients with stage 5 CKD (glomerular fi ltration rate [GFR] < 15 mL/min or receiving dialysis).…”
Section: Introductionmentioning
confidence: 99%
“…Its original name, nephrogenic fibrosing dermopathy, was changed to NSF once it became evident that fibrosis of other organs, including the heart, lungs, liver, lymph nodes, central nervous system, and muscle, also occurs (2,3). Since 2000, more than 200 cases have been reported worldwide, both in publications and to regulatory authorities (4).…”
mentioning
confidence: 99%